Demographic, health, and economic transitions and the future care burden. (April 2021) - King, Elizabeth M.; Randolph, Hannah L.; Floro, Maria S.; Suh, Jooyeoun
Highlights: Care needs across countries depend on fertility rates, aging of the population, and the prevalence and causes of morbidity. A care dependency ratio measures future care needs relative to the potential future supply of caregivers. Time-use survey data indicate that future unpaid caregivers will be equivalent to one- to two-fifths of the labor force. Unless the gender division of family care work changes, women and girls will be providing four-fifths of future unpaid caregiving. To lessen the family's care burden, governments should invest in care programs, basic infrastructure, and measures to protect caregivers and recipients. Abstract: The COVID-19 pandemic has caused millions of infections and deaths worldwide, forced schools to suspend classes, workers to work from home, many to lose their livelihoods, and countless businesses to close. Throughout this crisis, families have had to protect, comfort and care for their children, their elderly and other members. While the pandemic has greatly intensified family care responsibilities for families, unpaid care work has been a primary activity of families even in normal times. This paper estimates the future global need for caregiving, and the burden of that need that typically falls on families, especially women. It takes into account projected demographic shifts, health transitions, and economic changes in order to obtain an aggregate picture of the care need relative to the potential supply of caregiving in low-, middle- and high-income countries. This extensive margin of the future care burden, however, does not capture the weight of that burden unless the quantity and quality of care time per caregiver are taken into account. Adjusting for care time given per caregiver, the paper incorporates data from time-use surveys, illustrating this intensive margin of the care burden in three countries that have very different family and economic contexts—Ghana, Mongolia, and South Korea. Time-use surveys typically do not provide time data for paid care services, so the estimates depend only on the time intensity of family care. With this caveat, the paper estimates that the care need in 2030 would require the equivalent of one-fifth to two-fifths of the paid labor force, assuming 40 weekly workhours. Using the projected 2030 mean wage for care and social service workers to estimate the hypothetical wage bill for these unpaid caregivers if they were paid, we obtain a value equivalent to 16 to 32 percent of GDP in the three countries.